Analysis of Master of Music recital: a report on Jacob Ter Velhuis’ Garden of Love, Barry Cockcroft’s Ku Ku, Conrad Beck’s Nocturne, and Alfred Desenclos’ Prelude, Cadence et Final - Davis, Brittney (Kansas State University, 2019)
The saxophone is an instrument that can be utilized in many different styles of music. The repertoire presented in this master’s report showcases important examples of pieces that vary with respect to style, time period, and pedagogical considerations. Alfred Desenclos’ Prelude, Cadence et Final and Conrad Beck’s Nocturne are important, original compositions for saxophone. Jacob Ter Veldhuis’ Garden of Love is an excellent example of a work for soprano saxophone and electronics. The saxophone can produce non-traditional sounds such as slaptongue and multiphonics. Barry Cockcroft’s Ku Ku requires the performer to utilize these extended techniques in order to produce unique tonal colors and effects. This master’s report, presented as extended program notes with respect to the works mentioned above, includes biographical information regarding the composers, a stylistic overview, and thoughtful performance considerations.
Keywords: Saxophone; Jacob TV; Barry Cockcroft; Conrad Beck; Alfred Desenclos; Recital